2020
DOI: 10.1088/1755-1315/475/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of corn silk (Zea mays L.) herbal drinks tea with vacuum drying method as antioxidant

Abstract: The demand for antioxidant beverages made from herbs in the community increases due to the increasing number of types diseases caused by free radicals. One type of potential herbs as antioxidant is corn silk, in the form of corn silk herbal drinks tea. The basic ingredients for making herbal tea drinks is the dried corn silk. However, the temperature and drying time was found to affect the characteristics of herbal tea drinks produced. The purpose of this study was to determine the effect of temperature and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…HPD samples had the lowest TFC (25.59 mg/g), which may be due to the longer drying time and higher humidity in the drying chamber leading to the decomposition of flavonoids. The study by Laeliocattleya et al (2020) also confirmed the decreasing flavonoid content with the increase of drying time. TTC was in the order of: SD> SMIR> TH-HAD> PVD> HPD, where the TTC value of SD samples (15.05 mg/g) was significantly higher than that of mechanically dried samples, and there was no significant difference between mechanically dried samples, which may be due to the lower drying temperature and milder conditions of SD, which caused less thermal damage to the samples.…”
Section: Bioactive Substances Of Wgh Analysismentioning
confidence: 54%
“…HPD samples had the lowest TFC (25.59 mg/g), which may be due to the longer drying time and higher humidity in the drying chamber leading to the decomposition of flavonoids. The study by Laeliocattleya et al (2020) also confirmed the decreasing flavonoid content with the increase of drying time. TTC was in the order of: SD> SMIR> TH-HAD> PVD> HPD, where the TTC value of SD samples (15.05 mg/g) was significantly higher than that of mechanically dried samples, and there was no significant difference between mechanically dried samples, which may be due to the lower drying temperature and milder conditions of SD, which caused less thermal damage to the samples.…”
Section: Bioactive Substances Of Wgh Analysismentioning
confidence: 54%
“…Program PKM ini didesain agar masyarakat di wilayah kelurahan Sungai Beliung kecamatan Pontianak Barat dapat memanfaatkan rambut jagung yang awalnya dianggap limbah menjadi produk teh (Gambar 1) dengan nilai ekonomis. Jagung khususnya buah, selama ini hanya dimanfaatkan sebagai bahan pangan dan ternyata bagian rambut jagungnya juga diketahui memiliki banyak khasiat (Laeliocattleya et al, 2020;Morshed & Islam, 2015;Nessa et al, 2012;Shalihah et al, 2020). Perumnas II Kecamatan Pontianak Barat.…”
Section: Hasil Dan Pembahasanunclassified
“…Rambut jagung (Zea mays L.) menyerupai benang/ rambut lembut dengan panjang sekitar 10-20 cm yang berwarna kuning muda atau kuning keemasan hingga coklat (Laeliocattleya et al, 2020;Syawal & Laeliocattleya, 2020). Rambut jagung mengandung asam jagung, resin, gula, dan serat yang dibutuhkan oleh tubuh.…”
unclassified